Improving of method for determination of the long fiber output for qualimetry of flax varieties - L. V. Pashina; E. L. Pashin (Аграрная наука Евро-Северо-Востока, 2016)
An analysis of the reasons for non-compliance of long fiber output at flax stock processing on scutching-and-breaking machine and on the laboratory machine according to GOST 24383-89 was done. Among the reasons there are a line of conditions of trusts preparation to treatment and its implementation. With this in mind, as well as the previously received theoretical model, a new method is proposed for processing on a laboratory machine - at the initial filing of butt sections. On an experimental batch aligned along the length of the stems, fiber yield on the laboratory machine according to the State Standard and to the new method consistents with control (factory set). If there is a significant portion of short stems in raw materials, than approximately doubled to control excedded fiber output is fixed at laboratory machine according to GOST; there is the correspondence to control at processing by the new method. At processing of trusts of six flax varieties by three methods different values of yield in comparison with the processing at the factory unit in favor of the proposed method, on average, 17% are determined. The correlation coefficient between the output of the long fibers in a control and laboratory machine at the initial processing of butt portions is 0.68. The proposed method - the initial processing of butt areas at the processing of the trusts on a lab machine, is a way to minimize the differences in the estimates of the output of long fiber in the factory unit and a laboratory machine according to GOST. The latter is especially important when there is a significant portion of short stems.